PURCHASE DECISION PROCESS AT SHUKAKU BBQ, SHABU & AGEMONO, B ANDUNG BASED ON SOCIAL MEDIA AND PRODUCT DIVERSITY - Andiestian, Anzie; Abiyo, Benediktus Krisna; Taryadi, Dani; Junaedi; Analta, Resna; Samoedra, Artarina D.A. (CENTRAL ASIA AND THE CAUCASUS, 2022)
The phenomenon that is happening is that there are currently many restaurants that apply the all you can eat concept, one of which is Shukaku BBQ, Shabu & Agemono Bandung, which is located in the city of Bandung. This restaurant is supported by good use of social media in promoting and providing a variety of food and beverages that can be enjoyed by consumers. The restaurant's hope is that by using social media as a means of promotion properly and providing a variety of products, it is able to improve purchasing decisions. However, what happened to Shukaku BBQ, Shabu & Agemono Bandung was not as expected because the purchasing decision for Shukaku BBQ, Shabu & Agemono Bandung was low. The research method used is descriptive and verification methods. The sample used is the people of Bandung City. The results show that social media affects the purchasing decision process and product diversity affects the purchasing decision process and social media and product diversity simultaneously affect the purchasing decision process at Shukaku BBQ, Shabu & Agemono Bandung.